(untitled) (Journal of Gender and Social Issues, 2016)
This research aimed to explore how female students of a secondary school of Pakistan can be engaged in Argumentation about a Socio-Scientific Issue. An intervention was designed and carried out using Tolmin Model of Argumentation. The intervention consisted of three consecutive lessons in a senior secondary class of a girls’ government school in Karachi. Allocated time for each lesson was sixty minutes. There were 39 students in the class. A selected socio scientific issue was explicitly taught with the help of different teaching strategies based on Tolmin Model of Argumentation. The results of the study showed that there was a visible improvement in the scientific knowledge and argumentation skills of female students. This study presents significant insight into students’ conceptual understanding and argumentations skills for policy and practice.